Swim! how a shark, a suckerfish, and a parasite teach you leadership, mentoring, and next level success - Bond, Walter 1969- (Wiley, 2019)
"The author will make the book a centerpiece for his speaking business: Walter Bond has already started audience-testing the concepts in this book and incorporating feedback. Once published, he'll promote the book and its concepts throughout his business. - Author Plan for Moving Books Through Speaking Engagements and Keynotes: Each year, up to 100 times a year, Walter Bond and his team stand in front of packed audiences, sparking passion, influencing attitudes and shifting mindsets to lead companies towards change. With crowds often reaching over 1,000 attendees, Walter's messages have already impacted thousands of lives, and this book will influence even more. On some occasions, Walter has stepped out onto a stage in front of 25,0000 to inspire, engage and motivate individuals and companies to shift their mindset from compliance to excellence. Walter Bond will incorporate the book and its strategies into trainings, workshops and professional career development. This book will be more than a book; it will be a tool that business leaders, network marketers, entrepreneurs and coaches can use to inspire their team and teach about the power of mentorship, leadership, self-awareness, and teamwork. - PR: With close to 24,000 social media followers and another 18,000 in Bond's database, Walter Bond and his team have a strong social media and online presence. From Facebook and YouTube to Instagram and LinkedIn, Walter stays connected with his audiences far after his keynote presentations are over. His previous book, All Buts Stink! sold 60,000 copies (author reported)"--
"A business fable". - Description based on print version record and CIP data provided by publisher
Keywords: Business presentations; Leadership; Success in business; Présentations (Affaires); Succès dans les affaires; BUSINESS & ECONOMICS; General